Acrylonitrile catalyst as well as preparation method and application thereof
By preparing catalysts containing elements such as molybdenum, bismuth, nickel, tungsten, thallium, vanadium, phosphorus, etc., the problems of the existing catalysts being reduced selectivity and insufficient wear resistance after long-term operation are solved, and efficient, stable and highly selective acrylonitrile production is achieved.
Patent Information
- Application Number
- CN202411922598.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-04
AI Technical Summary
The existing acrylonitrile catalysts have reduced selectivity after long-term operation, increased by-products, and insufficient wear resistance when used in fluidized bed reactors, resulting in a decrease in production efficiency and product quality.
By preparing a catalyst containing elements such as molybdenum, bismuth, nickel, tungsten, thallium, vanadium, phosphorus, etc., using silica sol and molecular sieve as support, combining vapor-phase silica powder and structural guide agent, spray-drying and calcining treatment, a microsphere catalyst with excellent catalytic properties and stability was prepared.
This catalyst exhibits high conversion, good selectivity and stability in the propylene ammonia oxidation reaction, low by-products, high wear resistance, and is suitable for industrial production.
Abstract
Description
Technical Field
[0001] The invention relates to an acrylonitrile catalyst and a preparation method and application thereof, in particular to a microsphere catalyst for preparing acrylonitrile by an ammoxidation method in a fluidized bed, including a preparation method and an application process thereof, and belongs to the technical field of chemical industry. Background Art
[0002] Acrylonitrile is a very important basic organic raw material. It is the raw material monomer for synthetic fiber acrylic, and is also the raw material for thermoplastic synthetic resins such as acrylonitrile-butadiene-styrene (ABS), styrene-acrylonitrile (SAN), nitrile rubber, adiponitrile, acrylamide and other derivatives. The process technology of producing acrylonitrile by propylene ammoxidation has been developed and improved for more than 60 years and has become increasingly mature. The catalyst is the technical core of the process. Therefore, the development of a catalyst with excellent performance for preparing acrylonitrile by propylene ammoxidation is the technical focus of the acrylonitrile industry.
[0003] There are two main types of catalysts for industrial propylene ammoxidation to acrylonitrile: molybdenum-bismuth catalysts and antimony catalysts. Among them, molybdenum-bismuth catalysts are the mainstream catalysts, with a market share of more than 90%, which has led to most research work focusing on this series of catalysts. The number of technical patents disclosed and reported on this series of catalysts is considerable, such as foreign patent documents USP3746657, USP4228098, USP4264476, USP5093299, USP5175334, USP5212137, USP5457223, USP5466857, JK96-27089, WO9625391, etc.
[0004] Since the implementation of the patent system in China in 1985, there have been a large number of prior art disclosures involving acrylonitrile catalysts, such as CN87103645A, CN1005248A, CN100566829C, CN107282060A, CN109772356A, CN115501882A, CN106582695A, CN116618060A, CN117323999A, etc. In addition to molybdenum and bismuth, chemical formulas of different element combinations are formed by adding different other elements, which constitute a large number of patent technology applications.
[0005] Among these numerous existing technologies at home and abroad, there are methods of improving the oxidation-reduction performance of the catalyst by introducing metal components with variable valence states, such as iron, and accelerating the recovery of the effective state of the active components of the catalyst; of improving the structure and stability of the catalyst by introducing metal elements with different ionic radii, such as chromium, nickel, magnesium, manganese, zinc, aluminum, etc., which act as structural and electronic additives; of increasing the amount of lattice oxygen in the catalyst and improving the catalytic performance of the catalyst by introducing rare earth elements; and of improving the selectivity and activity of the catalyst by introducing elements such as cesium, rubidium, phosphorus, boron, aluminum, etc., to modify the surface of the catalyst and adjust the acidity and alkalinity.
[0006] For example, the acrylonitrile synthesis catalyst disclosed in CN1031661A is composed of molybdenum, bismuth and one or more of several groups of modifying elements, and can have both high conversion rate and good acrylonitrile selectivity under low ammonia consumption, and greatly reduce the generation of acrolein. The acrylonitrile catalyst disclosed in CN1031662A is composed of molybdenum, bismuth, iron, chromium, manganese and one or more of several groups of modifying elements, and has high activity and selectivity for acrylonitrile generation, and can also produce abundant hydrocyanic acid without reducing the yield.
[0007] The catalyst for preparing acrylonitrile by ammoxidation of propylene disclosed in CN113828337A is composed of silicon dioxide as a carrier and molybdenum, bismuth, iron, nickel, magnesium, sodium, strontium elements, and multiple elements selected from lithium, rubidium, cesium, and manganese, chromium, antimony, phosphorus, tungsten, samarium, thallium, cerium, etc., and can adapt to high-pressure and high-load operation and maintain a high acrylonitrile yield. However, there is no specific example of using thallium in the embodiments. The catalyst containing iron, bismuth, molybdenum and calcium disclosed in CN1131725C lists many elements including vanadium in its chemical expression, but there is no specific example of using vanadium in the embodiments. In these prior arts, the special catalytic performance that thallium and vanadium elements can play has not been demonstrated. CN107029700A adopts hydrothermal synthesis in a reactor, filtration and calcination under nitrogen to prepare molybdenum vanadium oxide (MoVO) with different crystal phases, but the catalyst prepared is used for preparing acrylonitrile by ammoxidation of propane, not a molybdenum-bismuth acrylonitrile catalyst for ammoxidation of propylene, and the reaction process is different.
[0008] In actual industrial applications, it is found that the selectivity of acrylonitrile catalysts after long-term operation is often significantly reduced due to various reasons such as low specific surface area, structural damage, loss of active components, etc., and the byproducts of deep oxidation such as carbon oxides will be significantly increased. Therefore, in addition to the existing disclosures of a large number of element combinations and different chemical formula expressions, there are also many disclosures and reports on carrier technology. Silica as a carrier is undoubtedly a more commonly used carrier material in acrylonitrile catalysts.
[0009] For example, CN1114915A discloses a catalyst more suitable for fluidized bed production of acrylonitrile, wherein the carrier silica is prepared from silica sol as raw material, wherein the average particle diameter of the silica sol is 10-200 nanometers and the sodium content is 100-2500 micrograms / gram, and the prepared catalyst has the advantages of high wear resistance, good catalytic activity, simple preparation steps and easy control. CN105597774A and CN05664962A also disclose the use of silica sol-derived silica carriers, which solve the low selectivity and poor stability of propylene ammoxidation reaction in the prior art by optimizing the electronegativity of the catalyst surface, and improve the operating load. However, silica sol carriers often have small specific surface area and low pore volume, which can easily limit the catalytic performance of the active component.
[0010] CN113828337A discloses a catalyst for preparing acrylonitrile by propylene ammoxidation, and its preparation method and application. In the catalyst pore distribution, pores with a pore diameter of 5 to 20 nanometers account for more than 40% of the total pore volume. A structure directing agent is used in the preparation method. When the catalyst is used for preparing acrylonitrile by propylene ammoxidation, not only is the propylene conversion rate high, but also the selectivity and stability can be improved.
[0011] CN101284237A discloses a catalyst for acrylonitrile production, wherein organic substances such as tetraethylamine, tetrapropylamine, polyacrylamide, ethyl silicate and a template agent are added to a carrier, and the preparation method includes aging, spray forming, thermal decomposition, crystal phase conversion and activation roasting process steps. The prepared catalyst has good reduction resistance, wear resistance, activity, selectivity and stability.
[0012] Some prior art also uses alumina and montmorillonite, diatomite and other carrier modifiers in the silicon dioxide carrier, such as a propylene ammoxidation process for preparing acrylonitrile catalyst disclosed in CN107398285, in which carrier modifiers such as montmorillonite and diatomite are added during the preparation process, which is conducive to improving the problem of poor selectivity and low stability of the catalyst. A method for preparing a highly efficient and wear-resistant acrylonitrile catalyst disclosed in CN106955717A is to add nano inorganic non-metallic materials such as activated clay or montmorillonite, and place it in a roasting furnace to roast and shape under the condition of maintaining a uniform temperature rise in stages to obtain an acrylonitrile catalyst. CN106955717A also discloses a method for preparing a highly efficient and wear-resistant acrylonitrile catalyst, which is to prepare the catalyst by combining a nano inorganic non-metallic material slurry with a method of maintaining a uniform roasting in stages.
[0013] Since some inorganic non-metallic materials used in the prior art lack stable and uniform structures and are difficult to disperse uniformly in the slurry, the particle size and structural uniformity of the final catalyst are poor, and it is not conducive to the long-term stable operation of the catalyst. CN116060083A discloses a catalyst for preparing acrylonitrile and its preparation method and application, including pre-loading metal oxides such as iron, cobalt, and nickel in the pores of a modified molecular sieve, and still having the advantages of good stability and high selectivity under high load.
[0014] Although a large number of improved catalyst preparation methods have been reported in the prior art, since the activity, selectivity and stability of the catalyst are involved when used in a fluidized bed reactor, it is necessary to reduce the loss of active components such as molybdenum, adjust and exert the catalytic efficiency of metal active components, and inhibit the side reactions of generating impurities such as carbon oxides, acrolein and acrylic acid, solve the problems of changes in the catalyst carrier structure, increase the production load and the wear resistance of the catalyst, etc., and continuous improvement research is still needed to further improve the catalyst's ammonia oxidation catalytic activity, product selectivity and operating stability. Summary of the invention
[0015] The object of the present invention is to provide an improved acrylonitrile catalyst and a preparation method thereof, so that the catalyst has better reaction activity, selectivity and stability, reduces by-products, and improves its wear resistance when used in a fluidized bed reactor.
[0016] The present invention provides an acrylonitrile catalyst and a preparation method thereof, comprising the following contents: (1) mixing solutions of molybdenum and bismuth compounds at a Mo / Bi molar ratio of 0.5 to 3 to prepare bismuth molybdate (A) containing α phase and / or γ phase; (2) synthesizing a pentasil type molecular sieve (B) with a Si / V molar ratio of 50 to 150 using a silicon source, an organic amine and a vanadium compound; (3) mixing silica sol with a molybdenum compound solution at a Si / Mo molar ratio of 0.5 to 1, and then sequentially adding solutions of nickel, tungsten and thallium compounds, as well as phosphoric acid, the molecular sieve (B) and the bismuth molybdate (A) to increase the molybdenum and tungsten content in the catalyst to 0.5 to 1. The weight percentage of bismuth, nickel, tungsten, thallium, vanadium and phosphorus in terms of oxides is (37-38): (4-6): (3-5): (2-3): (0.2-0.3): (0.1-0.3): (0.7-0.8); (4) adding fumed silica powder so that SiO2 in the catalyst accounts for 45wt%-55wt% on a dry basis; (5) beating and homogenizing, spray drying and forming at an outlet temperature of 150-180°C, and calcining at an air atmosphere of 550-680°C for 1-6 hours; and obtaining an acrylonitrile catalyst for use in a fluidized bed propylene ammoxidation reaction.
[0017] The present invention provides an acrylonitrile catalyst and a preparation method thereof. The preferred preparation conditions of the bismuth molybdate are as follows: acidic solutions of molybdenum and bismuth compounds are mixed at a temperature of 20 to 70° C. and a pH value of 1 to 7 with a Mo / Bi molar ratio of 0.5 to 1.5 to prepare bismuth molybdate containing an α phase and / or a γ phase; the most preferred condition is that the bismuth molybdate is prepared at a temperature of 30 to 50° C. and a pH value of 1 to 5 with a Mo / Bi molar ratio of 0.5 or 1.5 to prepare bismuth molybdate containing a γ phase and / or an α phase.
[0018] When acidic solutions of molybdenum and bismuth compounds are mixed to prepare γ-phase and / or α-phase-containing bismuth molybdate, the molybdenum compound is selected from molybdenum trioxide, molybdic acid and ammonium molybdate; preferably, ammonium molybdate is used; and the bismuth compound is selected from its soluble salts, preferably, bismuth nitrate is used.
[0019] The present invention provides an acrylonitrile catalyst and a preparation method thereof. The molecular sieve synthesis process is to stir and mix the silicon source, the organic amine and the vanadium oxide into a uniform colloid at a molar ratio of organic amine / SiO2=0.1-0.4, SiO2 / V2O5=30-200, H2O / SiO2=20-40, and hydrothermally crystallize at 130-180°C for 2-6 days to synthesize a pentasil type molecular sieve with a silicon-vanadium molar ratio of 50-150, preferably a pentasil type molecular sieve with a silicon-vanadium molar ratio of 50-100. The silicon source is selected from silica gel and / or silica sol; the vanadium oxide is selected from vanadium pentoxide; the organic amine is selected from one or more of ethylenediamine, n-butylamine, tetraethylammonium hydroxide and tetrapropylammonium hydroxide; preferably tetraethylammonium hydroxide or tetrapropylammonium hydroxide.
[0020] The present invention provides an acrylonitrile catalyst and a preparation method thereof. The nickel, tungsten and thallium compounds are selected from their water-soluble acids and salt compounds; preferably, their nitrates, nickel nitrate, tungsten nitrate and thallium nitrate are used.
[0021] The present invention provides an acrylonitrile catalyst and a preparation method thereof, wherein the catalyst for preparing acrylonitrile by propylene ammoxidation obtained by the above preparation method and preparation process is characterized in that the catalyst has an average particle size of 40 to 60 microns, an average pore size of 5 to 10 nanometers, a pore volume of 0.2 to 0.5 mL / g, and a surface area of 30 to 100 m 2 / g, bulk density is 0.5-1g / mL, and the abrasion resistance loss of the catalyst mechanical strength is ≤2.5%; preferably ≤2%.
[0022] In the preparation method of an acrylonitrile catalyst provided by the present invention, the dilution with deionized water involved in the preparation process is mainly to meet the requirements and convenience of operation, and has no effect on the performance of the final finished catalyst; when the convenience of operation is not affected, the minimum amount of water is used for dilution as much as possible, which can greatly reduce the energy consumption during drying.
[0023] The present invention also provides a method for preparing acrylonitrile by ammoxidation of propylene, comprising: in the presence of the catalyst prepared by the above preparation method, in a fluidized bed reactor, subjecting propylene to an ammoxidation reaction to obtain acrylonitrile as a product. The reaction conditions include: a reaction temperature of 400-450°C, a reaction pressure of 0.01-0.15 MPa in gauge pressure, and a weight hourly space velocity of 0.04-0.1 h -1 , the molar ratio of propylene: ammonia: air with O2 is 1: (1~1.5): (2~10).
[0024] The chemicals involved in the present invention are commonly used industrial chemical products and experimental reagents, which can be easily obtained through commercial purchase. The chemical unit operations involved in the present invention are conventional operating techniques in the art, which are well known to those of ordinary skill in the art and are routinely used in chemical experiments and industrial production processes.
[0025] The beneficial effects of the present invention are as follows: the preparation method of the catalyst provided and the catalyst obtained thereby, in the reaction process of preparing acrylonitrile by propylene ammoxidation, have very good catalytic reaction performance and stability, low by-products, good selectivity, good wear resistance during use, and are particularly suitable for industrial stable production processes.
[0026] Other features and advantages of the present invention will be described in more detail in the following specific embodiments and examples. DETAILED DESCRIPTION
[0027] The following examples are used to further describe the content and use effects of the present invention. The examples are provided as illustrative explanations of the embodiments of the present invention, but are not intended to limit the broad interpretation of the present invention.
[0028] In the embodiments, atomic emission spectroscopy and X-ray fluorescence are used to determine the content of elements; X-ray diffraction is used to determine the crystalline phase of the compound and the crystallinity of the molecular sieve and the content in the catalyst; low-temperature nitrogen adsorption is used to determine the specific surface area, pore volume and pore size; a laser particle size analyzer is used to determine the particle size of the catalyst; an abrasion strength instrument is used to determine the strength; and the composition of the raw materials and reaction products is analyzed by gas chromatography.
[0029] For other analytical tests, please refer to the relevant analytical methods in (National Standard for Test Methods for Petroleum and Petroleum Products, published by China Standards Press in 1989) and (Petrochemical Analysis Methods (RIPP Test Methods), published by Science Press in 1990).
[0030] Example 1
[0031] This embodiment is to illustrate that according to the requirements of the present invention, the α-phase bismuth molybdate and the γ-phase bismuth molybdate required for the catalyst are first prepared.
[0032] Ammonium molybdate (chemically pure, Beijing Chemical Reagent Company) was dissolved in deionized water to form an ammonium molybdate solution, bismuth nitrate (chemically pure, Beijing Chemical Reagent Company) was added to the deionized water, and nitric acid (chemically pure, Beijing Chemical Reagent Company) was used to acidify and dissolve it into a bismuth nitrate solution, and the ammonium molybdate solution was added to the bismuth nitrate solution under stirring at a Mo / Bi molar ratio of 3:2 and 1:2, respectively, and the solution temperature was kept below 50° C., to prepare a bismuth molybdate solution containing an α phase and a bismuth molybdate solution containing a γ phase, respectively.
[0033] Example 2
[0034] This embodiment is to illustrate that according to the requirements of the present invention, the vanadium-containing silicon molecular sieve required for the catalyst carrier part is first prepared.
[0035] According to the ratio of SiO2:0.015VO2:0.16TPAOH:37H2O, the calculated amount of tetrapropylammonium hydroxide aqueous solution (chemically pure, 40wt%, Beijing Daxing Xingfu Chemical Reagent Research Institute) and vanadium pentoxide (chemically pure, Beijing Chemical Reagent Company) were weighed and dissolved in deionized water, and the calculated amount of silica sol (industrial product, SiO220wt%, Qingdao Ocean Chemical) was added, and after stirring and mixing at room temperature, the obtained reaction mixture was charged into a stainless steel reactor with a polytetrafluoroethylene liner, crystallized at 130°C for 5 days, and the crystallized product was obtained by filtering and washing. The data of X-ray diffraction showed that the product was a molecular sieve with a pentasil structure, with a relative crystallinity of 85% and a silicon-vanadium molar ratio of about 60.
[0036] Example 3
[0037] This example illustrates the preparation of a catalyst for preparing acrylonitrile by ammoxidation of propylene according to the requirements of the present invention.
[0038] Silica sol (same as above) and ammonium molybdate solution (same as above) were mixed at a Si / Mo molar ratio of 0.9, and then nickel nitrate (chemically pure, Beijing Chemical Reagent Company), tungsten nitrate (chemically pure, Beijing Chemical Reagent Company), thallium nitrate solution (chemically pure, Beijing Chemical Reagent Company), and phosphoric acid (chemically pure, Beijing Chemical Reagent Company), the vanadium-containing silicon molecular sieve of Example 2, and the γ-phase bismuth molybdate solution of Example 1 were added in sequence. The ratio of molybdenum, bismuth, nickel, tungsten, thallium, vanadium and phosphorus in the catalyst in terms of oxide percentage by weight was 37.2:5:4:2.5:0.28:0.2:0.75. Fumed silica powder (industrial product, Qingdao Ocean Chemical) was added under stirring to make SiO2 in the catalyst account for 50wt% on a dry basis; after beating and grinding in a stirred mill for 2 hours, the catalyst was spray-dried in a small spray drying tower in the laboratory to form a microsphere catalyst with an average particle size of 40 microns, the tail gas outlet temperature of the drying tower was 180°C, and the catalyst was calcined at 670°C under air atmosphere for 1 hour; the catalyst of Example 3 used in the fluidized bed propylene ammoxidation reaction to prepare acrylonitrile was obtained, the average particle size of the catalyst was 49 microns, the average pore size was 5.2 nanometers, the pore volume was 0.33mL / g, and the surface area was 42m 2 / g, bulk density is 0.91g / mL, and catalyst abrasion resistance is 1.9%.
[0039] Example 4
[0040] The preparation content and operation steps are the same as those of Example 3, but the bismuth molybdate added is the α-phase bismuth molybdate solution prepared in Example 1, to obtain the catalyst of Example 4. The prepared catalyst of Example 4 has an average particle size of 51 microns, an average pore size of 5.1 nanometers, a pore volume of 0.35 mL / g, and a surface area of 41 m 2 / g, bulk density is 0.94g / mL, and the abrasion resistance of the catalyst is 1.8%.
[0041] Comparative Example 1
[0042] This comparative example is to prepare a catalyst containing molybdenum, bismuth and phosphorus on a silicon carrier according to the preparation content and steps of Example 1 in the classic patent document USP3746657, as the catalyst of Comparative Example 1; the average particle size of the catalyst of Comparative Example 1 prepared is 50 microns, the pore volume is 0.1 mL / g, and the surface area is 31 m 2 / g, bulk density is 0.98g / mL, and catalyst abrasion resistance is 2.6%; it is used for comparison with the catalysts prepared in Examples 3 and 4 of the present invention.
[0043] Comparative Example 2
[0044] This comparative example is a catalyst containing molybdenum, bismuth, nickel, tungsten, phosphorus and potassium on a silicon carrier prepared according to a relatively classic preparation method of the prior art. According to the preparation steps and methods of comparative example 1, the composition of molybdenum, bismuth, nickel, tungsten and phosphorus on the silicon carrier is close to the composition of the catalysts in Examples 3 and 4 of the present invention. In order to better reflect the characteristics of the classic prior art, according to the preparation content and steps of Example 3 in the patent document USP3746657, it contains the same amount of potassium element, and the prepared catalyst is used as the catalyst of comparative example 2; the average particle size of the catalyst is 47 microns, the pore volume is 0.1 mL / g, and the surface area is 32 m 2 / g, bulk density is 0.97g / mL, and catalyst abrasion resistance is 2.7%; the catalyst is used for comparison with the catalysts of Examples 3 and 4 of the present invention.
[0045] Comparative Example 3
[0046] This comparative example is for the purpose of comparing and illustrating with the comparative catalysts which are the same or similar in composition to Examples 3 and 4 of the present invention. A catalyst containing molybdenum, bismuth, nickel, tungsten, vanadium, thallium and phosphorus on a silicon carrier is prepared according to the preparation methods and steps of the more classic prior art. In order to better compare and illustrate the contents of the present invention, molybdenum, bismuth, nickel, tungsten, vanadium, thallium and phosphorus are loaded on a silicon carrier according to the preparation steps and methods of Comparative Examples 1 and 2, and the composition is as close as possible to that of the catalysts of Examples 3 and 4 of the present invention, to prepare a catalyst as Comparative Example 3; the catalyst of Comparative Example 3 has an average particle size of 44 microns, a pore volume of 0.1 mL / g and a surface area of 29 m 2 / g, bulk density is 0.99g / mL, and catalyst abrasion resistance is 2.9%; the catalyst is used for comparison with the catalysts of Examples 3 and 4 of the present invention.
[0047] Comparative Example 4
[0048] This comparative example is to prepare a catalyst containing a molecular sieve having structural characteristics similar to that of the catalyst of the present invention. According to the preparation method disclosed in the prior art, a comparative catalyst containing a ZSM-5 molecular sieve carrier modifier was prepared.
[0049] In order to better compare and illustrate the content of the present invention, the preparation steps and methods of Comparative Examples 5 to 7 in CN107282094B are selected, and the composition and composition of the catalysts in Examples 3 and 4 of the present invention are as close as possible. According to the content and steps of the examples in the classic literature of USP3702886, ZSM-5 molecular sieves are prepared and obtained, and used to further prepare the corresponding acrylonitrile catalyst as the catalyst of Comparative Example 4. For the convenience of comparison, the molecular sieve content in the catalyst of Comparative Example 4 is similar to the molecular sieve content in the catalysts in Examples 3 and 4 of the present invention. The average particle size of the catalyst of Comparative Example 4 prepared is 46 microns, the pore volume is 0.30 mL / g, and the surface area is 48 m 2 / g, bulk density is 0.96g / mL, and catalyst wear resistance strength is 2.5%; the catalyst is used as a contrast agent to make further comparative explanations on the content and technical effects of the present invention.
[0050] Example 5
[0051] This example compares the performance of the catalyst of the present invention and the comparative catalyst by means of a reaction evaluation test of a propylene ammoxidation process. The catalyst evaluation test was carried out on a small fluidized bed reactor with a sample load of 400 g and an inner diameter of 35 mm for laboratory use. The composition of the propylene raw gas used was such that the content of propylene by volume was not less than 99.9%.
[0052] Reaction evaluation conditions: reaction temperature 435°C, reaction pressure normal pressure, weight hourly space velocity 0.05h -1 The molar ratio of propylene: ammonia: air in terms of O2 is 1: 1.2: 10. The evaluation results are shown in Table 1 for the reaction evaluation data of preparing acrylonitrile by ammoxidation of propylene in a fluidized bed.
[0053] Table 1: Fluidized bed propylene ammoxidation evaluation test results of catalysts of Examples 3 to 4 and catalysts of Comparative Examples 1 to 4
[0054] catalyst Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Acrylonitrile single-pass yield / % 83.0 82.9 79.8 80.2 74.6 73.4 Propylene conversion rate / % 99.5 99.6 96.2 96.4 97.2 99.9 Acrylonitrile selectivity / % 83.4 83.2 82.9 83.1 76.7 73.5 Carbon oxides single-pass yield / % 14.1 14.3 15.8 16.1 17.2 17.8
[0055] By selecting the catalysts of Example 3 of the present invention and Comparative Example 2, a 50-day stability evaluation comparison test was conducted. In terms of the stability of propylene conversion activity and the stability of product acrylonitrile selectivity, the catalyst of Example 3 of the present invention was 1 to 3 percentage points better than the comparative catalyst.
[0056] It is thus shown that, compared with the prior art, the catalyst provided by the present invention has both a higher conversion rate and good acrylonitrile selectivity, and has good stability. Since the reaction temperature that can be used is relatively low, byproducts such as carbon monoxide, carbon dioxide and other organic carbon-containing substances are lower. It is shown that the catalyst obtained by the preparation method of the catalyst of the present invention has better catalytic reaction activity and selectivity, as well as reaction stability in the reaction process of preparing acrylonitrile by propylene ammoxidation. In addition, since the mechanical strength of the catalyst of the present invention is good, it is more suitable for the industrialized acrylonitrile production process of long-cycle operation, and thus the use of the catalyst in industry will be able to achieve better economic benefits.
[0057] It should be noted that the above embodiments are only used to illustrate the technical solution of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing an acrylonitrile catalyst, characterized in that: The invention comprises the following contents: (1) mixing solutions of molybdenum and bismuth compounds at a Mo / Bi molar ratio of 0.5 to 3 to prepare bismuth molybdate (A) containing α phase and / or γ phase; (2) synthesizing a pentasil type molecular sieve (B) with a Si / V molar ratio of 50 to 150 using a silicon source, an organic amine and a vanadium compound; (3) mixing silica sol with a molybdenum compound solution at a Si / Mo molar ratio of 0.5 to 1, and then sequentially adding solutions of nickel, tungsten and thallium compounds, as well as phosphoric acid, the molecular sieve (B) and the bismuth molybdate (A) to make the molybdenum, bismuth, nickel, tungsten, thallium, vanadium and phosphorus in the catalyst to form a catalyst with oxygen. The weight percentage ratio of the catalyst is (37-38): (4-6): (3-5): (2-3): (0.2-0.3): (0.1-0.3): (0.7-0.8); (4) adding fumed silica powder so that the SiO2 in the catalyst accounts for 45wt%-55wt% on a dry basis; (5) after beating and homogenizing, spray drying and forming at an outlet temperature of 150-180°C, and calcining at an air atmosphere of 550-680°C for 1-6 hours; the obtained catalyst is used in the reaction process of preparing acrylonitrile by ammoxidation of propylene in a fluidized bed.
2. The method for preparing an acrylonitrile catalyst according to claim 1, characterized in that: The bismuth molybdate is prepared by mixing acidic solutions of molybdenum and bismuth compounds at a Mo / Bi molar ratio of 0.5 to 1.5 at 30 to 50° C. and a pH value of 1 to 5 to prepare bismuth molybdate containing α phase and / or γ phase.
3. The method for preparing an acrylonitrile catalyst according to claim 2, characterized in that: The molybdenum compound is selected from molybdenum trioxide, molybdic acid and ammonium molybdate; and the bismuth compound is selected from bismuth nitrate.
4. The method for preparing an acrylonitrile catalyst according to claim 1, characterized in that: The process for synthesizing molecular sieves is as follows: in molar ratios: organic amine / SiO2=0.1-0.4, SiO2 / V2O5=30-200, H2O / SiO2=20-40, silicon source, organic amine and vanadium oxide are stirred and mixed into a uniform colloid, and hydrothermally crystallized at 130-180°C for 2-6 days to synthesize a pentasil type molecular sieve with a silicon-vanadium molar ratio of 50-100.
5. The method for preparing an acrylonitrile catalyst according to claim 3, characterized in that: The silicon source is selected from silica gel and / or silica sol; the vanadium oxide is selected from vanadium pentoxide; and the organic amine is selected from one or more of ethylenediamine, n-butylamine, tetraethylammonium hydroxide and tetrapropylammonium hydroxide.
6. The method for preparing an acrylonitrile catalyst according to claim 1, characterized in that: The nickel, tungsten and thallium compounds are nitrates thereof.
7. A catalyst for preparing acrylonitrile by ammoxidation of propylene, characterized in that: The method is prepared by any one of claims 1 to 6.
8. A catalyst for preparing acrylonitrile by ammoxidation of propylene according to claim 7, characterized in that: The catalyst has an average particle size of 40 to 60 microns, an average pore size of 5 to 10 nanometers, a pore volume of 0.2 to 0.5 mL / g, and a surface area of 30 to 100 m 2 / g, bulk density is 0.5-1g / mL, and the abrasion resistance loss of the catalyst mechanical strength is ≤2%.
9. A method for preparing acrylonitrile by ammoxidation of propylene, comprising: In the presence of the catalyst according to any one of claims 7 or 8, propylene is subjected to an ammoxidation reaction in a fluidized bed reactor to obtain acrylonitrile as a product.
10. The method for preparing acrylonitrile by ammoxidation of propylene according to claim 9, characterized in that: The reaction conditions also include: reaction temperature 400-450°C, reaction pressure 0.01-0.15 MPa, weight hourly space velocity 0.04-0.1 h -1 , the molar ratio of propylene: ammonia: air calculated as O2 is 1: (1~1.5): (2~10).
Citation Information
Patent Citations
Catalyst for preparing acrylonitrile by ammonia oxidizing method
CN100566829C
Preparation method of catalyst for acrylonitrile fluid bed
CN101284237A
Synthetic catalyst for propenyl nitrile
CN1031661A
Catalyst for propenyl nitrile prepn. with a high prodn of hydrocyanic acid
CN1031662A
Catalyst used for preparing acrylonitrile
CN105597774A
Cited By
Process method for preparing acrylonitrile through propylene ammoxidation
CN120097865A
Acrylonitrile catalyst, and preparation method therefor and use thereof
WO2026137653A1
Process method for preparing acrylonitrile by means of propylene ammoxidation
WO2026166003A1